Lightning Generation in Moist Convective Clouds and Constraints on the Water Abundance in Jupiter. Issue 2 (18th February 2021) - Aglyamov, Yury S.; Lunine, Jonathan; Becker, Heidi N.; Guillot, Tristan; Gibbard, Seran G.; Atreya, Sushil; Bolton, Scott J.; Levin, Steven; Brown, Shannon T.; Wong, Michael H.
Abstract: Recent Juno observations have greatly extended the temporal and spatial coverage of lightning detection on Jupiter. We use these data to constrain a model of moist convection and lightning generation in Jupiter's atmosphere, and derive a roughly solar abundance of water at the base of the water cloud. Shallow lightning, observed by Juno (Becker et al., 2020, https://doi.org/10.1038/s41586‐020‐2532‐1, Nature, 584, 55–58) and defined as flashes originating at altitudes corresponding to pressure less than 2 bars, is reproduced, as is lightning at a deeper range of pressures, including those below the water cloud base. It is found that the generation of lightning requires ammonia to stabilize liquid water at altitudes corresponding to sub‐freezing temperatures. We find a range of local water abundances in which lightning is possible, including subsolar values of water—consistent with other determinations of deep oxygen abundance. Plain Language Summary: Many missions to Jupiter have detected lightning in its atmosphere, but the Juno mission now in orbit has made the most extensive observations on where, and the rate at which, lightning flashes occur. Lightning on Earth is the discharge of electricity that happens when positive and negative charges separate between raindrops and small ice particles in towering thunderheads, somewhat like how combing a cat's fur can create a static electric discharge. This same process is thought to occur in Jupiter's atmosphere, though with some important differences, and we model that process here. Comparing our model with the Juno data also supports the idea that ammonia is in Jupiter's thunderheads, dissolving some of the water ice and increasing the abundance of raindrops. Key Points: A model of the generation of lightning is applied to Jupiter, constrained by Juno data; the model reproduces well terrestrial rates The model allows for lightning at moderately subsolar abundances of water if ammonia is present The model produces lightning at shallow altitudes (heights above 2 bars) while also producing lightning at deeper levels seen by Galileo